Effectiveness of the E-PBB Application in Increasing Taxpayer Compliance in Banyuwangi Regency - Adawiya, Qori'atul; Surati, Nu'man Hakki Barruka; Siswanto, Adil (Jurnal Pengabdian Masyarakat, 2025)
Purpose: The e-PBB (Land and Building Tax) application in Banyuwangi aims to increase ease and efficiency in the tax payment process for public, as well as increase awareness of tax obligations Method: This Community Service uses a qualitative approach by collecting data through surveys and interviews with e-PBB application users. Data analysis is carried out to provide user experience and the effectiveness of the application in facilitating tax payments. Practical Applications: The e-PBB application allows taxpayers to make online payments, check bills, and get tax-related information easily. This not only reduces queues at the tax office, but also increases transparancey in local tax management. Conclusion: The research results show that the e-PBB application in Banyuwangi has succeeded in increasing tax compliance and facilitating access to information for the public. By implementing this technology, it is hoped that it can encourage active community participation in fulfilling tax obligations, as well as supporting an increase in local original income (PAD) for better development.